2017
DOI: 10.3389/fmicb.2017.00528
|View full text |Cite
|
Sign up to set email alerts
|

Functional Characterization and Conditional Regulation of the Type VI Secretion System in Vibrio fluvialis

Abstract: Vibrio fluvialis is an emerging foodborne pathogen of increasing public health concern. The mechanism(s) that contribute to the bacterial survival and disease are still poorly understood. In other bacterial species, type VI secretion systems (T6SSs) are known to contribute to bacterial pathogenicity by exerting toxic effects on host cells or competing bacterial species. In this study, we characterized the genetic organization and prevalence of two T6SS gene clusters (VflT6SS1 and VflT6SS2) in V. fluvialis. Vfl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
63
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 36 publications
(71 citation statements)
references
References 57 publications
7
63
1
Order By: Relevance
“…The highest transcript levels of hcp1 and VP1388 occurred at an OD 600 value of 0.6 and 0.8, respectively, due to the QS regulation ( Figure 1 ), suggesting V. parahaemolyticus T6SS1 functions only during the mid-logarithmic growth phase. Similar observations have been reported in other species, including Yersinia pseudotuberculosis ( Zhang et al, 2011 ), V. cholerae ( Ishikawa et al, 2009 ), V. alginolyticus ( Sheng et al, 2012 ), V. anguillarum ( Tang et al, 2016 ), and V. fluvialis ( Huang et al, 2017 ). Notably, the highest expression levels of AphA and ToxR occurred at an OD 600 value of 0.05 to 0.2, whereas that of OpaR occurred at 0.4–0.6.…”
Section: Discussionsupporting
confidence: 87%
“…The highest transcript levels of hcp1 and VP1388 occurred at an OD 600 value of 0.6 and 0.8, respectively, due to the QS regulation ( Figure 1 ), suggesting V. parahaemolyticus T6SS1 functions only during the mid-logarithmic growth phase. Similar observations have been reported in other species, including Yersinia pseudotuberculosis ( Zhang et al, 2011 ), V. cholerae ( Ishikawa et al, 2009 ), V. alginolyticus ( Sheng et al, 2012 ), V. anguillarum ( Tang et al, 2016 ), and V. fluvialis ( Huang et al, 2017 ). Notably, the highest expression levels of AphA and ToxR occurred at an OD 600 value of 0.05 to 0.2, whereas that of OpaR occurred at 0.4–0.6.…”
Section: Discussionsupporting
confidence: 87%
“…4 A ), T6SS1 may be active under different conditions compared with T6SS2. Indeed, other Vibrio species show T6SS activity that is conditionally regulated ( 13 , 33 , 84 ), and future work will need to explore how free-living versus host-like conditions modulate V. fischeri T6SS gene expression and function. Alternatively, T6SS1 may be used to interact with eukaryotic cells ( 15 , 28 , 72 ).…”
Section: Discussionmentioning
confidence: 99%
“…The T6SS operating is energetically costly to bacterial cells, so its gene cluster is tightly controlled to adapt its expression and assembly to changing environmental conditions ( Journet and Cascales, 2016 ). Environmental cues, such as temperature ( Ishikawa et al, 2012 ; Salomon et al, 2013 ; Huang et al, 2017 ), salinity/osolarity ( Ishikawa et al, 2012 ; Huang et al, 2017 ), iron limitation ( Brunet et al, 2011 ), stresses ( Gueguen et al, 2013 ), cell lysates ( LeRoux et al, 2015 ) etc., affect the expression of T6SS in various species. At present, VasH is the first identified T6SS regulator encoded within the Vibrio cholerae T6SS major cluster, which works as a transactivator of T6SS in V. cholerae together with σ 54 ( Bernard et al, 2011 ; Kitaoka et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…We previously sequenced the whole genome of a clinical isolate of V. fluvialis , an emerging foodborne pathogen of increasing public health concern, whose sequence analysis revealed the existence of T6SS homologous gene clusters ( Lu et al, 2014 ). Subsequently, we characterized the organization, function, and expression regulation of T6SS in V. fluvialis ( Huang et al, 2017 ). We showed that one of the two T6SSs, termed VflT6SS2, is functionally active under low (25°C) and warm (30°C) temperatures.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation